Konstruksi Moderasi Beragama Dalam Tinjauan Agama Islam dan Konghucu: Studi Komparatif Kitab Suci Al-Quran dan Sishu Wujing - Yuliawati, Tita; Anwar, Zaeni; Ridlo, Muhammad Abdurrasyid; Fadhlurrahman, Zulfi (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2025)
Religious moderation does not belong to a particular religion alone, but is a value that exists in various religions and civilizations of the world. This study aims to explore the concept of religious moderation and analyze the role of moderation from the perspective of the Qur'an and Sishu Wujing in preventing religious conflict. With a comparative approach to the Qur'an and Sishu Wujing, this research explores the views of moderation contained in both sources as guidelines for peaceful coexistence. Through understanding the values of religious moderation, it is hoped that concrete strategies can be formulated to promote inter-religious harmony and prevent conflict. This research concludes that religious moderation is very important, especially in the current era, where the goal is to produce a generation that is moderate and not easily influenced by radicalism spread through cyberspace. In both Islam and Confucianism, both religions uphold a sense of tolerance, with the belief that differences are an unavoidable reality and should be a source of strength to complement each other, not to divide.